The role of the lateral amygdala in the retrieval and maintenance of fear-memories formed by repeated probabilistic reinforcement - Erlich, Jeffrey C.; Bush, David E.; LeDoux, Joseph E. (Frontiers in Behavioral Neuroscience, 2012)
The lateral nucleus of the amygdala (LA) is a key element in the neural circuit subserving Pavlovian fear conditioning, an animal model of fear and anxiety. Most studies have focused on the role of the LA in fear acquisition and extinction, i.e. how neural plasticity results from changing contingencies between a neutral conditioned stimulus (e.g. a tone) and an aversive unconditioned stimulus (e.g. a shock). However, outside of the lab, fear memories are often the result of repeated and unpredictable experiences. Examples include domestic violence, child abuse or combat. To better understand the role of the LA in the expression of fear resulting from repeated and uncertain reinforcement, rats experienced a 30% partial reinforcement fear-conditioning schedule four days a week for four weeks. Rats reached asymptotic levels of conditioned fear expression after the first week. We then manipulated LA activity with drug (or vehicle) infusions once a week, for the next three weeks, before the training session. LA infusions of muscimol, a GABA-A agonist that inhibits neural activity, reduced conditioned stimulus (CS) evoked fear behavior to pre-conditioning levels. LA infusions of pentagastrin, a cholecystokinin-2 (CCK) agonist that increases neural excitability, resulted in CS-evoked fear behavior that continued past the offset of the CS. This suggests that neural activity in the LA is required for the retrieval of fear memories that stem from repeated and uncertain reinforcement, and that CCK signaling in the LA plays a role in the recovery from fear after the removal of the fear-evoking stimulus.